Design considerations of future short haul transport aircraft - Howe, D. (Cranfield University, 1976)
The rapid escalation of air transport in the past two decades has resulted in difficulties associated with airport congestion and ground trip delays. These have been particularly acute for short haul operations. Suggestions have been made that they might be alleviated by the use of smaller airfields located nearer to population centres than existing large airports which operate aircraft specifically designed for the purpose. This paper reports a systematic investigation of the requirements, design parameters and performance characteristics of short haul transport aircraft. Designs intended for operation- in the VTOL, STOL, RTOL or CTOL modes have been considered and compared in an attempt to predict the more promising prospects for the future. A number of specific design studies were used as the basis for the comparison of the weight, economic and noise characteristics of the aircraft concepts which fall into the categories investigated.